The Types, Interpretations and Functions of Myth - Mazurkiewicz, Michał (Respectus Philologicus, 2012)
In this article, the author analyses the phenomenon of myth—a significant element of culture—by presenting miscellaneous types of myths that have accompanied human beings from the dawn of time to the present, interpreting them from the point of view of (for example) philosophy or psychoanalysis, the functions of myths, and their ways of influencing human beings in the contemporary world. Myths are complex cultural phenomena, difficult to assess unambiguously. One of the main reasons is the fact that they are not only holy tales having some religious background; we can also talk about secular myths, for example in art or in sport. As far as our contemporary world—brazenly hi-tech and filled with the spirit of logos—is concerned, it is an interesting fact that myths do not surface but remain hidden, as it were; they are in many cases a subconscious way of seeing things. It depends on the individual whether he or she somehow notices those wisdoms existing somewhere under the mask of the world, industrialized and permeated by unemotional technology as it is. Without a shadow of a doubt, myths fulfil many important functions—they are a wonderful source of wisdom, teach people humility, and give hope and strength in difficult periods. Undoubtedly, they are not—as some people would probably prefer—mere relics of a distant past. The forms of myths may, however, evolve. Looking closely into this phenomenon, one can notice that myths may occur (in different realms of life) in somewhat changed, modernized forms. The author of this article has based his analysis on numerous works of a group of illustrious researchers who specialize in exploring the phenomenon of myth, e.g., among others: Bronisław Malinowski (a Polish anthropologist, one of the most important anthropologists of the 20th century), Mircea Eliade (a Romanian historian of religion, one of the leading interpreters of religious experience), and Sigmund Freud (an Austrian neurologist, founder of the discipline of psychoanalysis).
Keywords: myth; mythology; religion; psychoanalysis